Pediatric Hypertension: Provider Perspectives - Jennifer K. Bello MD, MS; Nivedita Mohanty MD; Victoria Bauer BS; Sarah S. Rittner MA; Goutham Rao MD (SAGE Publishing, 2017)
Pediatric hypertension is a risk for adult cardiovascular disease, making early detection important. The prevalence of pediatric essential hypertension is rising due to the increased prevalence of obesity. Though guidelines for screening, diagnosis, evaluation, and management are available, there are barriers to accurate diagnosis of pediatric hypertension, including lack of knowledge and complexity of blood pressure standards. We aimed to gain insights into reasons for low rates of diagnosis and treatment from primary care providers. As part of a multisite randomized controlled trial, we interviewed 8 providers in a community health center network. We used a grounded theoretical approach to analyze transcripts. Providers reflected on numerous barriers to diagnosis, management, and follow-up; recommendations for educational content; and how community health center systems can be improved. Findings informed development of a multifaceted intervention. Despite lack of training on essential hypertension, providers were comfortable recommending lifestyle changes to promote healthier weight and reduced blood pressure.